A comprehensive method of assessing routine CT scans in schizophrenia - Smith, G. N. (1997)
Morphological brain abnormalities are common in schizophrenia, although the aetiological and clinical significance of these findings is largely unknown. Substantial between-subject variability suggests that large samples are needed to study the full implications of brain pathomorphology. Computerized tomography (CT) is frequently used routinely in schizophrenia, and large numbers of scans are available for study. This article describes the development and statistical properties of a rapid and simple method of assessing CT scans. The CT Rating Scale for Schizophrenia (CTRSS) is minimally affected by variability in scanning procedures, is reliable, and accurately estimates area and volumetric measures of brain spaces. By promoting the comprehensive assessment of large numbers of routinely obtained scans, the CTRSS would allow the investigation of variables that may systematically affect results (e.g. gender and age) and variables with low prevalence. The CTRSS provides a useful adjunct to technologically more sophisticated methods of assessment such as magnetic resonance imaging (MRI).